2012
DOI: 10.5539/cis.v5n2p98
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Rural Library Usage among Rural Youth in Malaysia: Its Corresponding Determinants and Impacts

Abstract: The demands for information are increasing nowadays, providing adequate sources of information for the community is a crucial agenda as it is an essential part of community development particularly the youth; the future leader of our community. As information and communication technology (ICT) play significant roles as sources of information, similarly, the rural library in Malaysia can play the same roles in offering updated and needed information of the community. The main objective of this paper is to know … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Asia, research from Malaysia (Yusop et al 2013), Bangladesh (Islam 2006) and India (Bachhav 2012;Omar et al 2012;Thanuskodi & Pandiselvi 2014) showed that the information needs of rural dwellers in these countries are largely concerned with agriculture in general, medical and health matters, education development, religion, culture and business, among others. In Africa, research from South Africa (Jiyane 2002:16;Maepa 2000), Botswana (Mutshewa et al 2010:4) and Tanzania (Mtega & Ronald 2013:69) has shown that the information needs of rural dwellers revolved around various areas, such as pension, business, crime, agriculture, transport, proper housing, transport and communication systems and basic healthcare.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In Asia, research from Malaysia (Yusop et al 2013), Bangladesh (Islam 2006) and India (Bachhav 2012;Omar et al 2012;Thanuskodi & Pandiselvi 2014) showed that the information needs of rural dwellers in these countries are largely concerned with agriculture in general, medical and health matters, education development, religion, culture and business, among others. In Africa, research from South Africa (Jiyane 2002:16;Maepa 2000), Botswana (Mutshewa et al 2010:4) and Tanzania (Mtega & Ronald 2013:69) has shown that the information needs of rural dwellers revolved around various areas, such as pension, business, crime, agriculture, transport, proper housing, transport and communication systems and basic healthcare.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Information seeking is one of the most common online activities for young people and can lead to extra information networks, which may develop their sustainable livelihood. Information and knowledge-seeking among youth have varied significantly as they wish to pursue virtual information (Omar et al, 2012). Youths use ICTs to search for information about livelihood opportunities available to them.…”
Section: Information Seekingmentioning
confidence: 99%
“…To further promote the enhancement of knowledge and information seeking among rural residents, rural libraries, or Perpustakaan Desa, have been introduced by the government to provide library services to the rural population (Omar et al, 2012a). Rural libraries are small facilities located in rural areas that serve to provide several information sources and library services to local communities in the area.…”
Section: Rural Libraries In Malaysiamentioning
confidence: 99%